Acquisition of “Start” and “Stop” response thresholds in peak-interval timing is differentially sensitive to protein synthesis inhibition in the dorsal and ventral striatum - MacDonald, Christopher; Cheng, Ruey-Kuang; Meck, Warren H. (Frontiers in Integrative Neuroscience, 2012)
Time-based decision-making in peak-interval timing procedures involves the setting of response thresholds for the initiation (‘Start’) and termination (‘Stop’) of a response sequence that is centered on the target duration. We report here that the acquisition of the ‘Start’ response depends on de novo protein synthesis in the dorsal striatum (DS), but not the ventral striatum (VS). Conversely, inhibition of protein synthesis in the VS, but not the DS, impairs the acquisition of the ‘Stop’ response. The hypothesis is that the dorsal and ventral regions of the striatum function as a competitive neural network that encodes the temporal boundaries marking the beginning and end of a learned response sequence.